Mechanisms of action of cytoplasmic microRNAs. Part 6. MicroRNA-mediated translation activation - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2022)
In the scientific review, the mechanisms of action of cytoplasmic miRNAs, namely miRNA-mediated activation of translation, are given. To write the article, information was searched using Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library databases. Examples of direct activation of mRNA translation by miRNA are presented. One of them is miRNA-mediated activation of translation, which is associated with the peculiarities of the state of the cell (resting cell effect). It has been shown that protein 1 of the fragile X mental retardation (FMR1) syndrome, depending on the stage of the cell cycle, can participate in both inhibition and enhancement of translation. It is known that microRNAs can influence the activity of RNP by binding to the RNA-binding sites of specific mRNAs or directly to RBP molecules, directly inhibiting their activity. Poly (rC) binding protein 2 (PCBP2) is a multifunctional adapter molecule that binds to RNA and DNA, competing with other RNA-binding factors. The PCBP2 protein limits translation initiation by preventing ribosome recruitment. The authors provided information on miR-346-mediated activation of the translation of receptor-interacting protein 140. It is emphasized that some miRNAs, preventing the degradation of the mRNA molecule, increasе the level of its stability, which is accompanied by an enhancement in their translation. MicroRNAs stabilize specific mRNA targets, preventing the association of the ARE element degradation factor, tristetraprolin, with mRNA. Data are presented on the activation of mRNA target translation by factors that sequester miRNAs or compete with miRNAs. Various intracellular factors and proteins can enter into a competitive relationship with miRNA and interfere with or remove it from the target mRNA. It is known that activation of translation can occur due to microRNA inhibition of repressor proteins. The authors indicate that increased miR-145 expression is accompanied by activation of myocardin translation, which induces the proliferation and migration of smooth muscle cells.